Accommodating a mega-festival: the Āti Atti Varatar Vaipavam festival in Kanchipuram - Hüsken, Ute (Religion, 2023)
As public performances, festivals celebrate what people believe, who people are, and project what people want to be. Festivals are an important medium by which cultural, social, and religious identities are represented and negotiated. This is especially pronounced in exceptional festival events which require much more improvisational skills than ‘routine’ festival occasions. This contribution discusses one such event: In 2019, the Varadarāja temple in Kanchipuram celebrated a rare and long-awaited festival, called Āti Atti Varatar Vaipavam, which takes place only once in 40 years. When the number of visitors increased in unanticipated ways soon after the festival started, time-tested ritual rules were suspended, and new stakeholders started to determine the performance of the festival. This contribution traces the multiple ways in which the festival’s mythological background and its performance were contested, and how the sheer number of attending pilgrims effected long-lasting changes in the social dynamics among the temple’s stakeholders.